INTEGRASI NILAI-NILAI ISLAM DALAM PEMBELAJARAN IPS DI MTSS UMMUL QURA AMUNTAI - Imam Dhia Ul Islam (Adisam Publisher, 2025)
General learning which is integrated with Islamic values has made learning more interesting, students look more serious and active in participating in their learning. Based on this statement, this study aims to find out how to integrate Islamic values in social studies learning at MTSS Ummul Qura Amuntai and what Islamic values are integrated in social studies learning at MTSS Ummul Qura Amuntai. The subjects in this study were 1 social studies teacher at MTSS Ummul Qura Amuntai. The techniques used in data collection are interviews, observation, and documentaries. Then it is processed through the process of data reduction, data display, and data verification. Meanwhile, to analyze the data the author uses descriptive and qualitative analysis. After the data is analyzed, it can finally beconcluded that the integration of Islamic values in social studies learning at MTSS Ummul Qura Amuntai can be concluded, that; 1) Social studies teachers have integrated Islamic values in their learning. Every material presented is integrated with Islamic values, such as human material as a social being, material in the universe, historical material, and other materials. 2) Social studies teachers have integrated Islamic values in their learning. As for the integrated Islamic values, such as establishing good relationships with others in accordance with Islamic teachings, maintaining social harmony, mutual respect for one another, giving to one another, and also helping each other. Other Islamic values also include good behavior or rights among others, not offending anyone, being grateful for the blessings of Allah SWT, and having faith in Him.